2014
DOI: 10.1002/dta.1680
|View full text |Cite
|
Sign up to set email alerts
|

Doping control analysis of trimetazidine and characterization of major metabolites using mass spectrometric approaches

Abstract: Since January 2014, the anti-anginal drug trimetazidine [1-(2,3,4-trimethoxybenzyl)-piperazine] has been classified as prohibited substance by the World Anti-Doping Agency (WADA), necessitating specific and robust detection methods in sports drug testing laboratories. In the present study, the implementation of the intact therapeutic agent into two different initial testing procedures based on gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) is reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 24 publications
5
34
0
Order By: Relevance
“…Several double blind quality control samples (dbEQAS) were introduced with other samples to the laboratory and appropriately identified. It is interesting to note that one of the reported adverse analytical findings (AAF) was trimetazidine, a compound added to the Prohibited list just before the Games in 2014…”
Section: Resultsmentioning
confidence: 99%
“…Several double blind quality control samples (dbEQAS) were introduced with other samples to the laboratory and appropriately identified. It is interesting to note that one of the reported adverse analytical findings (AAF) was trimetazidine, a compound added to the Prohibited list just before the Games in 2014…”
Section: Resultsmentioning
confidence: 99%
“…Routine doping control urine samples were prepared for initial testing purposes regarding stimulants according to established protocols described elsewhere . Instrumental analysis was conducted employing gas chromatography‐mass spectrometry (GC‐MS) with simultaneous acquisition of a nitrogen‐phosphorus detector (NPD) signal.…”
Section: Methodsmentioning
confidence: 99%
“…Both assays proved fit‐for‐purpose with LODs concerning trimetazidine of 0.5 ng/mL respectively 14 ng/mL, and controlled elimination studies indicated detection windows of > 24 h after a single therapeutic dose of the coronary vasodilator. Until its inclusion in the list of prohibited substances in January 2014, the prevalence of trimetazidine use among athletes resulted in up to 39 identifications per year or 0.23% of findings …”
Section: Hormone and Metabolic Modulatorsmentioning
confidence: 99%